Carbon Nanotubes: High‐Temperature Operating Non‐volatile Memory of Printable Single‐Wall Carbon Nanotubes Self‐Assembled with a Conjugate Block Copolymer (Small 6/2013). Issue 6 (15th March 2013) - Hwang, Sun Kak; Choi, Jae Ryung; Bae, Insung; Hwang, Ihn; Cho, Suk Man; Huh, June; Park, Cheolmin
<x xml:space="preserve">Abstract</x> C. Park and co‐workers develop high‐performance, printable, non‐volatile polymer memories with solution‐processed nanocomposite films of a conjugated block copolymer, poly(styrene‐block‐paraphenylene) (PS‐b‐PPP), and single‐walled carbon nanotubes (SWNTs). The devices, described on page 831, show excellent reliability of both data retention over time and read/write cycle endurance at high temperatures of up to 100 °C without significant performance degradation. This arises from the strong, non‐destructive, and isomorphic π–π interactions between the SWNTs and the PPP block. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>